Clinical assessment of the diabetic patient with retinopathy in a hemodialysis program. dialysis unit lara II (Salud, Arte y Cuidado, 2022)
With the objective of describing the clinical evaluation, visual acuity and treatment of patients with Diabetic Retinopathy who attend the Hemodialysis program at the Lara II Dialysis Unit, a descriptive and cross-sectional study was carried out, the technique corresponds to a field investigation using the assessment of patients, with direct data collection. The results of the physical evaluation in the population are predominantly male aged between 48 and 89 years, with systolic blood pressure between 180 and 100 mmHg, diastolic blood pressure between 80 and 40 mmHg, heart rate between 100 and 60 beats per minute, respiratory rate between 20 and 18 breaths per minute. Regarding the weight, it is between 38 kg and 103 kg. The size between 1.38cm and 1.84 cm, and abdominal circumference between 78 cm and 103 cm. In relation to the diagnostic test for visual acuity, there is a predominance of visual acuity of 20/200 both in the right eye and in the left eye, and on pharmacological and non-pharmacological treatment it was evidenced that 32% of patients maintain control of the pathology based on in performing relevant paraclinics, and only 16% perform routine physical activity, as well as adequate nutritional care. Regarding drug treatment, 74% used oral hypoglycemic agents, 79% maintained the use of insulin, and 47% received intravitreal injections. It is concluded that the physical assessment that the clinical values ​​are within normal limits in some cases, being favorable to prevent the evolution of the pathology, in the diagnosis of visual acuity there is poor control of diabetes, which has brought retinopathy as a complication diabetes, as well as a late establishment of the diagnosis with an average of 10 years of evolution, without adequate control and treatment to prevent its progression.
Keywords: mellitus diabetes; diabetic retinopathy